1997
DOI: 10.1001/archsurg.1997.01430310067014
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β3 (TGFβ3) Accelerates Wound Healing Without Alteration of Scar Prominence

Abstract: Exogenous TGF beta 3 displays substantial vulnerary properties in wound healing and may be useful in treating nonhealing wounds. However, the observation that TGF beta 3 can reduce scarring was not confirmed in this study, and the messenger RNA level in response to TGF beta 3 suggests that it behaves similarly to TGF beta 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…However, to date, no regular 2D cell culture model has been able to show a significant difference in function between T1 and T3 (Guo et al, 2016; Wu et al, 1997). Therefore, to examine the difference in T1 and T3’s effect on the expression of SMA, we developed a 3D cell culture model, in which the cells secrete and interact with their own ECM, adding another layer of complexity to regular cell culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no regular 2D cell culture model has been able to show a significant difference in function between T1 and T3 (Guo et al, 2016; Wu et al, 1997). Therefore, to examine the difference in T1 and T3’s effect on the expression of SMA, we developed a 3D cell culture model, in which the cells secrete and interact with their own ECM, adding another layer of complexity to regular cell culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al (2003) have shown that decorin can prevent TGFβ1-induced muscle fibrosis but perhaps the most successful mediator of the effects of TGFβ1 has been the application of TGFβ3 (Ghosh et al 2006;Hosokawa et al 2003;Occleston et al 2009;Wu et al 1997). While TGFβ3 has not been shown to have direct effects on muscle repair, extensive research has shown TGFβ3 to be a potent inhibitor of scar tissue formation reducing the influx of inflammatory cells to the wound site without delaying wound healing (Wu et al 1997). The indirect effects of inhibiting TGFβ1 could plausibly result in enhanced progenitor cell proliferation, differentiation and recruitment, while decreasing scar tissue.…”
Section: Control Of the Regenerative Microenvironmentmentioning
confidence: 99%
“…Topical TGF-β1 stimulates wound repair in young ischaemic rabbit skin, but not in aged skin 80 . It does this in young rabbits by increasing the rate of granulation tissue formation, but without altering scar prominence 81 . There have been no reported trials using TGF-β in human wound healing, probably owing to the complexity of its actions and interactions, together with concern about neoplastic transformation of cells.…”
Section: Transforming Growth Factor βmentioning
confidence: 99%